2011
DOI: 10.1111/j.1582-4934.2009.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow‐derived cells can acquire cardiac stem cells properties in damaged heart

Abstract: Experimental data suggest that cell-based therapies may be useful for cardiac regeneration following ischaemic heart disease. Bone marrow (BM) cells have been reported to contribute to tissue repair after myocardial infarction (MI) by a variety of humoural and cellular mechanisms. However, there is no direct evidence, so far, that BM cells can generate cardiac stem cells (CSCs). To investigate whether BM cells contribute to repopulate the Kit+ CSCs pool, we transplanted BM cells from transgenic mice, expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…The small islands of cardiomyocytes within the C-ECM-patched area lacked syncytium, representing immature myocardium that was not capable of actively contributing to cardiac function. Possible sources of the cardiomyocytes are resident islet1-positive (isl1+) [Laugwitz et al, 2005;Bu et al, 2009] cells or circulating bone marrow mesenchymal stem cells [Barile et al, 2011;Mangi et al, 2003;Zantop, 2006], both of which have been shown to form cardioblasts. The possibility also exists that iatrogenic effects caused a limited seeding of both patches but that the cardiomyocytes were only able to populate the C-ECM due to the presence of cell attachment sites and rapid angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The small islands of cardiomyocytes within the C-ECM-patched area lacked syncytium, representing immature myocardium that was not capable of actively contributing to cardiac function. Possible sources of the cardiomyocytes are resident islet1-positive (isl1+) [Laugwitz et al, 2005;Bu et al, 2009] cells or circulating bone marrow mesenchymal stem cells [Barile et al, 2011;Mangi et al, 2003;Zantop, 2006], both of which have been shown to form cardioblasts. The possibility also exists that iatrogenic effects caused a limited seeding of both patches but that the cardiomyocytes were only able to populate the C-ECM due to the presence of cell attachment sites and rapid angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…12 Several reports suggest that acute cardiac injury involves the activation and recruitment of both resident cardiac progenitor cells and noncardiac progenitor cells from BM that home in to the site of injury. [13][14][15][16][17][18] In the absence of administration of external growth factors or progenitor cell therapies, the endogenous regenerative process is insufficient in a significant plurality, as evidenced by the occurrence of post-MI heart in ≈30% of patients. 19 Moreover, experimental studies have suggested the release of stem and progenitor cells into the circulation from BM niche, which could play an important role in the turnover of vascular endothelium and myocardial repair response after MI.…”
mentioning
confidence: 99%
“…(Klumpp et al). Since engineering of three-dimensional tissue of skeletal muscle asks for a large quantity of muscle cells, adult stem cells are a suitable cell source in TE research and regenerative medicine (Barile et al 2009, Mollmann et al 2009, Roche et al 2009). Therefore, mesenchymal stromal cells (MSC) are a feasible alternative cell source for skeletal muscle TE due to their high proliferation rates in vitro and their low imunogenicity in vivo (Chen, L. et al 2009) that even enables allogenic transplantation of MSCs (García-Castro J 2008, Rossignol et al 2009).…”
Section: Stem Cellsmentioning
confidence: 99%